Optical spectral transmission to monitor disease activity in arthritis patients: longitudinal follow-up comparison with clinical parameters - Triantafyllias, Konstantinos; Alhaddad, Mohammed; Baraliakos, Xenofon; Muthuraman, Muthuraman; Schwarting, Andreas (Rheumatology (Oxford, England), 2025)
To examine the longitudinal associations of optical spectral transmission (OST) with clinical inflammatory arthritis activity markers in order to investigate its potential in monitoring disease activity. OST measurements were performed in 1312 wrist and finger joints of 60 patients with clinical suspicion of inflammatory activity, within the context of known rheumatic inflammatory diseases at two separate time intervals. In each time point, patients underwent additional clinical and laboratory examinations. The change of OST values was statistically compared with changes in clinical activity parameters like DAS28 and swollen joint counts (SJC). Additionally, the diagnostic performance of OST was assessed in comparison to a historic control group (2508 joints of 114 healthy subjects) using receiver operating characteristics (ROC). The relationships between OST values, clinical and laboratory parameters, as well as patient characteristics, were evaluated through correlation analyses. Mean OST scores were significantly higher in the inflammatory arthritis group compared with the control group (P < 0.001). OST correlated significantly with clinical activity markers like DAS28, SJC and TJC in both time points (all; P < 0.05). Longitudinal changes of OST values (ΔOST) were significantly associated with changes in DAS28 (ΔDAS28) (r = 0.377; P = 0.004) and ΔSJC (r = 0.488; P < 0.001) over the same time period. The area under the curve of the baseline receiver operating characteristic curve was 0.781 (95%CI 0.82-0.94). OST was able to reliably assess disease activity and correlated longitudinally with arthritis activity markers, showing promising potential during monitoring of inflammatory arthritis.